Queer Jewish Lives Between Central Europe and Mandatory Palestine: Biographies and Geographies - Yonay, Yuval; Sluhovsky, Moshe; Kraß, Andreas (transcript, 2021)
When queer Jewish people migrated from Central Europe to the Middle East in the first half of the 20th century, they contributed to the creation of a new queer culture and community in Palestine. This volume offers the first collection of studies on queer Jewish lives between Central Europe and Mandatory Palestine. While the first section of the book presents queer geographies, including Germany, Austria, Poland and Palestine, the second section introduces queer biographies between Europe and Palestine including the sexologist Magnus Hirschfeld (1868–1935), the writer Hugo Marcus (1880–1966), and the artist Annie Neumann (1906-1955).